Improving the Ability of Analysis of Mirror Building Elements Through Cooperative Learning of Jigsaw Type Modeli Class Xi Students SMA Negeri 1 Tanjung Batu Ilir Ogan District - Desfriyanti; Wardarita, Ratu; Missriani (Jurnal Pendidikan Tambusai, 2021)
Based on the research findings, it can be concluded that there is an increase in the ability to analyze the elements of short story builders through the Jigsaw cooperative learning model in student’s XI class of MIPA-1 Senior High School 1 at Tanjung Batu of Ogan Ilir Regency. In the action cycle 1, the value obtained was 2160 with an average of 67.50. Students who complete as many as 14 people with an average percentage of completeness of 43.75%. In cycle 2 there was an increase where the achievement of the results obtained a value of 2280 with an average of 71.25. Students who complete as many as 26 students with an average percentage of completeness of 81.25%. Then in the action cycle 3 has increased again where the results obtained are 2535 with an average of 79.22. Students who complete as many as 30 students with an average percentage of completeness of 93.75%.